1993
DOI: 10.3109/02699059309008160
|View full text |Cite
|
Sign up to set email alerts
|

Methods of increasing client acceptance of a memory book

Abstract: This case history describes the successful use of a commercially available memory book by a brain injury survivor, including a description of the characteristics which made the book acceptable. Implications of the normalization principle for memory rehabilitation are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Reality testing helped LB see the impact that his difficulties were having on his everyday life and therefore highlighted the need for efficient compensatory strategies. The beneficial effect of reality testing is potentially generalisable to other patients who lack awareness and has already been reported by other authors (e.g., Fluharty & Priddy, 1993). LB reported feeling quite "technophobic" about electronic aids and struggled to use a mobile phone.…”
Section: Increasing Acceptancementioning
confidence: 64%
See 3 more Smart Citations
“…Reality testing helped LB see the impact that his difficulties were having on his everyday life and therefore highlighted the need for efficient compensatory strategies. The beneficial effect of reality testing is potentially generalisable to other patients who lack awareness and has already been reported by other authors (e.g., Fluharty & Priddy, 1993). LB reported feeling quite "technophobic" about electronic aids and struggled to use a mobile phone.…”
Section: Increasing Acceptancementioning
confidence: 64%
“…He also experienced anxiety, and was low in mood. Previous reports have suggested that mood can adversely influence the outcome of rehabilitation (Fluharty & Priddy, 1993;Malec, Schafer, & Jacket, 1992), therefore LB's mood was monitored throughout the present study.…”
Section: Methods Participant Lbmentioning
confidence: 99%
See 2 more Smart Citations
“…Though assistive devices can be invaluable, people with cognitive deficits may be reluctant to use them in public if this may label them as impaired or disabled [8,13]. As a result, there is often a stigma associated with assistive technologies [12], leading to lower acceptance rates of such devices.…”
Section: Acceptancementioning
confidence: 99%